2013
DOI: 10.1371/journal.pone.0069847
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles Deciphering Leaf Senescence Variation between Early- and Late-Senescence Cotton Lines

Abstract: Leaf senescence varies greatly among genotypes of cotton (Gossypium hirsutium L), possibly due to the different expression of senescence-related genes. To determine genes involved in leaf senescence, we performed genome-wide transcriptional profiling of the main-stem leaves of an early- (K1) and a late-senescence (K2) cotton line at 110 day after planting (DAP) using the Solexa technology. The profiling analysis indicated that 1132 genes were up-regulated and 455 genes down-regulated in K1 compared with K2 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 80 publications
(129 reference statements)
3
39
0
Order By: Relevance
“…The LHCB expression level in early-senescence cotton line was lower than in late-senescence cotton line. The chlorophyll content and photosynthesis in earlysenescence cotton line were also lower than in late-senescence cotton line at 95 and 110 days after planting, suggesting that the decreased chlorophyll content and photosynthesis in earlysenescence cotton might be attribute to reduced expression of LHCB (Kong et al, 2013). In the present study, expression of the GhLHCB in cotton leaves and the P n rate were decreased under waterlogging stress, suggested that the reduced GhLHCB expression might be an attribute to the reduction in P n rate.…”
Section: 2supporting
confidence: 46%
“…The LHCB expression level in early-senescence cotton line was lower than in late-senescence cotton line. The chlorophyll content and photosynthesis in earlysenescence cotton line were also lower than in late-senescence cotton line at 95 and 110 days after planting, suggesting that the decreased chlorophyll content and photosynthesis in earlysenescence cotton might be attribute to reduced expression of LHCB (Kong et al, 2013). In the present study, expression of the GhLHCB in cotton leaves and the P n rate were decreased under waterlogging stress, suggested that the reduced GhLHCB expression might be an attribute to the reduction in P n rate.…”
Section: 2supporting
confidence: 46%
“…At the transcriptional level, the regulation of senescence has been well studied in model species such as A. thaliana (Gepstein et al, 2003;Lim et al, 2003;Lin and Wu, 2004). Furthermore, this process has been partially assessed in other species such as rice (Lee et al, 2001), tobacco (Pageau et al, 2006), pea (Pic et al, 2002), wheat (Uauy et al, 2006), cotton (Kong et al, 2013), maize (Sekhon et al, 2012;Zhang et al, 2014), turnip (Gombert et al, 2006), barley (Hollmann et al, 2014;Jukanti et al, 2008) and sunflower (Cabello et al, 2006;Fernandez et al, 2012a;Moschen et al, 2014). Transcription factors (TFs) are key proteins in the regulation of gene expression and signal transduction networks regulating different biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that GhNAC18 may have a significant role in the young leaves. Although, NACs have been reported to be involved in early and late senescence in upland cotton (Kong et al, 2013), GhNAC18 seemed to have a different trend during aging process because, its transcript abudance decreases as aging advances. Premature leaf senescence causes poor or low yield in cotton in early maturing cultivars (Wright, 1998).…”
Section: Discussionmentioning
confidence: 95%